Stereoselective synthesis of 3-alkylidene/alkylazetidin-2-ones from azetidin-2,3-diones - Tiwari, Dharmendra Kumar; Shaikh, Ashif Y.; Pavase, Laxmikant S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2007)
Azetidin-2,3-diones have been used as synthons for the synthesis of C-3 alkylidene/alkylazetidin-2-ones. Some of the 3-alkylazetidin-2-ones are well known for their cholesterol absorption inhibitor activity. A regio and stereoselective Grignard reaction on a keto group followed by dehydration using PPh3/CCl4 reagent is a key step in this synthesis. Hydrogenation of the 3-alkylideneazetidin-2-ones provided stereoselectively cis-3-alkylazetidin-2-ones in very good yields. (c) 2006 Published by Elsevier Ltd.
Keywords: 3-diones; azetidin-2; azetidin-2-ones; beta-lactam; Grignard reaction

Facile synthesis of unusual glycosyl carbamates and amino acid glycosides from propargyl 1,2-orthoesters as glycosyl donors - Shaikh, Ashif Y.; Sureshkumar, Gopalsamy; Pati, Debasish; Sen Gupta, Sayam; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2011)
Propargyl 1,2-O-orthoesters are exploited for the synthesis of 1,2-trans O-glycosides of protected amino acids. N-Fmoc- and N-Cbz protected serine/threonine - benzyl/methyl esters reacted well with glucosyl-, galactosyl-, mannosyl- and lactosyl- derived propargyl 1,2-orthoesters affording respective 1,2-trans glycosides in good yields under AuBr(3)/4 angstrom MS Powder/CH(2)Cl(2)/rt. t-Boc serine derivative gave serine 1,2-orthoester and glycosyl carbamate. Optimized conditions enabled preparation of new glycosyl carbamates from N-Boc protected amines in a single step using gold catalysts and propargyl 1,2-orthoesters in excellent yields.

Synthesis of glycopolypeptides by the ring opening polymerization of O-glycosylated-alpha-amino acid N-carboxyanhydride (NCA) - Pati, Debasis; Shaikh, Ashif Y.; Hotha, Srinivas; Sen Gupta, Sayam (Polymer Chemistry, 2011)
The novel synthesis of O-glycosylated lysine-NCA from a stable glycosyl donor and a commercially available protected amino acid in very high yield is reported. These O-glycosylated lysine-NCA monomers underwent ring opening polymerization using simple primary amine initiators to form well defined, high molecular weight homoglycopolypeptides and diblock co-glycopolypeptides. The synthesis of azide labelled end functionalized glycopolypeptides and amphiphilic diblock copolypeptides is also reported. This methodology represents an easy and practical route to the synthesis of O-glycosylated polypeptides with 100% glycosylation.

Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Synthesis and self-assembly of amphiphilic homoglycopolypeptide - Dhaware, Vinita; Shaikh, Ashif Y.; Kar, Mrityunjoy; Hotha, Srinivas; Sen Gupta, Sayam (Langmuir, 2013)
The synthesis of the amphiphilic homoglycopolypeptide was carried out by a combination of NCA polymerization and click chemistry to yield a well-defined Polypeptide having an amphiphilic carbohydrate on its side chain. The amphiphilicity of the carbohydrate was achieved by incorporation of an alkyl chain, at the C-6 position of the carbohydrate thus also rendering the homoglycopolypeptide amphiphilic. The homoglycopolypeptide formed multimicellar aggregates in water above a critical concentration of 0.9 mu M due to phase separation. The multimicellar aggregates were characterized by DLS, TEM, and AFM. It is proposed that hydrophobic interactions of the aliphatic chains at the 6-position of the sugar moieties drives the assembly of these rod-like homoglycopolypeptide into large;spherical aggregates. These multimicellar aggregates encapsulate both hydrophilic as well as hydrophobic dye as was confirmed by confocal microscopy. finally, amphiphilic random polypeptides containing 10% and 20% alpha-D-mannose in addition to glucose containing a, hydrophobic alkyl chain at its 6 position were synthesized by our methodology, and these polymers Were also found to assemble into spherical nanostructures. The spherical assemblies Of amphiphilic random glycopolypeptides containing 10% and 20% mannose were found to be surface bioactive and were found, to interact with the lectin Con-A.

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.